HUBUNGAN ANTARA TINGKAT FANATISME TERHADAP PERILAKU KONSUMTIF FANS JKT48 (BENERPITU48) DI SALATIGA: HUBUNGAN ANTARA TINGKAT FANATISME TERHADAP PERILAKU KONSUMTIF FANS JKT48 (BENERPITU48) DI SALATIGA - Rahtri Nugraheni Budiyanti; Tritjahjo Danny Soesilo; Yustinus Windrawanto (STKIP Subang, 2025)
This study aims to determine the relationship between the level of fanaticism and consumptive behavior among members of the JKT48 fan community Benerpitu48 in Salatiga. The research employed a quantitative correlational approach with 85 respondents selected using purposive sampling. The research instruments consisted of a fanaticism scale (modified from Chung et al., 2005) and a consumptive behavior scale (adapted from Engel et al., 1994). Data were analyzed using Kendall’s tau_b test. The results showed that most respondents had high to very high levels of fanaticism, while the majority demonstrated low consumptive behavior. The correlation test produced a value of r = –0.421 with p < 0,01, indicating a significant negative relationship of moderate strength. These findings suggest that the higher the level of fanaticism, the lower the consumptive behavior of community members. This differs from previous studies stating that fanaticism triggers consumptive tendencies, leading to the conclusion that fanaticism in this community context functions as a protective factor.